2018
DOI: 10.1073/pnas.1714900115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanogenetics for the remote and noninvasive control of cancer immunotherapy

Abstract: While cell-based immunotherapy, especially chimeric antigen receptor (CAR)-expressing T cells, is becoming a paradigm-shifting therapeutic approach for cancer treatment, there is a lack of general methods to remotely and noninvasively regulate genetics in live mammalian cells and animals for cancer immunotherapy within confined local tissue space. To address this limitation, we have identified a mechanically sensitive Piezo1 ion channel (mechanosensor) that is activatable by ultrasound stimulation and integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 36 publications
2
145
0
1
Order By: Relevance
“…Additional pharmacological studies in invasive cancer cells suggested the involvement of IP3 receptors (IP3Rs) or TRP channels (Weitz et al, 2017), as suggested by others (Bootman et al, 2002;Diver et al, 2001;Xu et al, 2005). Nonfocused US also stimulates calcium signaling mediated by the Piezo1 mechanosensitive ion channel directly couple to microbubbles (Pan et al, 2018). Other ER-localized mechanosensitive channels (i.e.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additional pharmacological studies in invasive cancer cells suggested the involvement of IP3 receptors (IP3Rs) or TRP channels (Weitz et al, 2017), as suggested by others (Bootman et al, 2002;Diver et al, 2001;Xu et al, 2005). Nonfocused US also stimulates calcium signaling mediated by the Piezo1 mechanosensitive ion channel directly couple to microbubbles (Pan et al, 2018). Other ER-localized mechanosensitive channels (i.e.…”
Section: Introductionmentioning
confidence: 83%
“…Our previous work demonstrated that mechanosensory FUS-stimulation generates a robust Ca 2+ signaling response which can be used to distinguish invasive from non-invasive cancer cells (Hwang et al, 2013;Weitz et al, 2017). Others have also demonstrated mechanosensory Ca 2+ signaling responses using non-focused US-stimulation other contexts (Carina et al, 2018;Pan et al, 2018;Wood and Sehgal, 2015) as well as more general studies to clarify the physiological, cell biological and molecular mechanisms underlying mechanosensory dependent Ca 2+ signaling responses (Castellanos et al, 2016;Liu et al, 2017;Maresca et al, 2018;Tyler et al, 2008). Our Removing or lowering external Ca 2+ from culture medium did not eliminate FUS dependent Ca 2+ signaling (see Figure 1D).…”
Section: Discussionmentioning
confidence: 99%
“…Remote control of T cells by small-molecules or light 69,70 either require systemic administration or are limited by light penetration through tissue. By contrast, thermal targeting of tissues can be accomplished by several platforms 25 including focused ultrasound, which was recently demonstrated for control of T cell gene expression 71 or thermal control of bacteria engineered with temperature-sensitive repressors 72 . To provide T cells the capacity to respond to heat, we designed synthetic thermal gene switches comprised of arrays of heat shock elements upstream of a core promoter.…”
Section: Discussionmentioning
confidence: 99%
“…[6] However,c onstructing genetic circuits requires complex genetic manipulation of target cells and may disturb other biological processes. [7] To address this issue,c onsiderable efforts have been devoted to developing nongenetic approaches for directing cellular response using chemical or physical operations.P hysical stimuli utilizing optical, [8] ultrasound, [9] and magnetic actuations [10] have been engineered to regulate cellular signal transduction. These approaches directly act with the endogenous proteins and regulate cellular signal transduction in auser-defined manner.Nevertheless,most available methods were directed by only asingle input, which was limited by al ack of generic approaches to integrate multi-input simulation and satisfy the requirements for processing complex operations.…”
Section: Living Cells Continuously Sense Various Extracellular Signalsmentioning
confidence: 99%